On statistical mapping of poverty: Social reality, concepts and measurement - Sônia Rocha (Institute for Applied Economic Research (ipea), 2015)
This article concerns the need to define poverty in a way to be relevant to the context it is to refer, to be compatible with data availability and to be useful for policy purposes. It discusses the adequacy of concepts to different socioeconomic situations and analyses the two approaches to poverty - basic needs and income (or poverty line) - in what concerns their advantages and shortcomings. It highlights how perverse the generalization of the use of the poverty line approach can be, specially when applied to socioeconomic settings where income is an inadequate parameter of well-being and the data base is insufficient for its adequate operacionalisation.
Keywords: 330